Molekulárně epidemiologická charakteristika a diverzita Listeria monocytogenes v humánní populaci České republiky v letech 2013-2016 - Gelbíčová, T; Tomáštíková, Z; Karpíšková, R (Epidemiologie, mikrobiologie, imunologie, 2017)
Listeria monocytogenes is the cause of a serious foodborne infection with a high fatality rate. The aim of this study was to assess the diversity of human isolates of L. monocytogenes recovered in the Czech Republic from 2013 to 2016 by molecular biological methods. Most cases of listeriosis were caused by strains of serotype 1/2a (58 %) from clonal complex CC8 (28 %) and serotype 4b (28 %) from CC6 (16 %). The results of macrorestriction analysis confirmed primarily the occurrence of sporadic cases of listeriosis. A local outbreak of listeriosis was reported in the Moravian-Silesian Region. Real-time molecular subtyping methods have proved helpful in the investigation of Listeria outbreaks.
Keywords: Serotyping; Česká republika; lidé; Listeria monocytogenes; Molecular Typing; listeriosis - serotype - clonal complex - pulsotype - molecular epidemiology.; molekulární typizace; Humans; listeriové infekce; Listeriosis; sérotypizace; Czech Republic